S100A12 and S100A8/9 proteins are biomarkers of articular disease activity in Blau syndrome - Wang, Lin; Mackensen, Friederike (Rheumatology, 2018)
Objective: To identify biomarkers of articular and ocular disease activity in patients with Blau syndrome (BS). - Methods: Multiplex plasma protein arrays were performed in five BS patients and eight normal healthy volunteers (NHVs). Plasma S100A12 and S100A8/9 were subsequently measured by ELISA at baseline and 1-year follow-up in all patients from a prospective multicentre cohort study. CRP was measured using Meso Scale Discovery immunoassay. Active joint counts, standardization uveitis nomenclature for anterior uveitis cells and vitreous haze by Nussenblatt scale were the clinical parameters. - Results: Multiplex Luminex arrays identified S100A12 as the most significantly elevated protein in five selected BS vs eight NHVs and this was confirmed by ELISA on additional samples from the same five BS patients. In the patient cohort, S100A12 (n = 39) and S100A8/9 (n = 33) were significantly higher compared with NHVs (n = 44 for S100A12, n = 40 for S100A8/9) (P = 0.0000004 and P = 0.0003, respectively). Positive correlations between active joint counts and S100 levels were significant for S100A12 (P = 0.0008) and S100A8/9 (P = 0.015). CRP levels did not correlate with active joint count. Subgroup analysis showed significant association of S100 proteins with active arthritis (S100A12 P = 0.01, S100A8/9 P = 0.008). Active uveitis was not associated with increased S100 levels. - Conclusion: S100 proteins are biomarkers of articular disease activity in BS and potential outcome measures in future clinical trials. As secreted neutrophil and macrophage products, S100 proteins may reflect the burden of granulomatous tissue in BS.
Gesehen am 18.06.2019